2017
DOI: 10.1097/md.0000000000007090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine and midazolam for flexible fiberoptic bronchoscopy in intensive care unit patients

Abstract: This study aimed to investigate the clinical effectiveness of dexmedetomidine and midazolam for sedation of intensive care unit (ICU) patients requiring flexible fiberoptic bronchoscopy (FFB).This retrospective cohort study included 148 patients from the third ICU ward of the Second Affiliated Hospital of Harbin Medical University (Harbin, China) who received simultaneous invasive mechanical ventilation and FFB between March 2012 and December 2014. Patients were divided into dexmedetomidine (n  =  72) and mida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
0
16
1
1
Order By: Relevance
“…However, unfortunately, there are no clear recommendations favoring one sedation regimen over another. The introduction of new sedative drugs, such as remifentanil and dexmedetomidine, has added to the complexity of combining sedative regimens [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…However, unfortunately, there are no clear recommendations favoring one sedation regimen over another. The introduction of new sedative drugs, such as remifentanil and dexmedetomidine, has added to the complexity of combining sedative regimens [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Although the current guidelines recommend the combined use of an opioid and midazolam for bronchoscopy sedation [3], physicians often use a single drug, or a combination of benzodiazepines, propofol, and opioids in this setting [5,6]. In addition, with the development of new drugs, remifentanil and dexmedetomidine have been introduced as options for analgosedation for flexible bronchoscopy in adults [7][8][9][10][11]. Accordingly, the combination of new drugs and conventional drugs has enabled a wide variety of combinations of drugs to be used for analgosedation for flexible bronchoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the combination of new drugs and conventional drugs has enabled a wide variety of combinations of drugs to be used for analgosedation for flexible bronchoscopy. Several studies have demonstrated the safety and efficacy of the addition of remifentanil or dexmedetomidine (to conventional drugs) in adult patients who underwent flexible bronchoscopy [7][8][9][10]. However, the best-standardized practice for the use of sedation during bronchoscopy has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Although the current guidelines recommend the combined use of an opioid and midazolam for bronchoscopy sedation [3], physicians often use a single drug, or a combination of benzodiazepines, propofol, and opioids in this setting [5,6]. In addition, with the development of new drugs, remifentanil and dexmedetomidine have been introduced as options for analgosedation for flexible bronchoscopy in adults [7][8][9][10][11]. Accordingly, the combination of new drugs and conventional drugs has enabled a wide variety of combinations of drugs to be used for analgosedation for flexible bronchoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the combination of new drugs and conventional drugs has enabled a wide variety of combinations of drugs to be used for analgosedation for flexible bronchoscopy. Several studies have demonstrated the safety and efficacy of the addition of remifentanil or dexmedetomidine (to conventional drugs) in adult patients who underwent flexible bronchoscopy [7][8][9][10]. However, the best-standardized practice for the use of sedation during bronchoscopy has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%